Legal Review of Consumer Rights in Product Sales Through the Bundling System - Rohaedi, Rosalia Alima Utami; Susilowati Suparto; Elisatris Gultom (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
The study aims to determine consumer rights in product sales through an adverse bundling system and dispute resolution efforts to maintain rights. The focus of the problem is the fulfillment of consumer rights and their resolution, both in court and out of court. The method of research used by the author is normative juridical, which examines theories, concepts, legal principles, and laws and regulations related to the research topic. Novelty of this research is the gap in the implementation of product sales strategies carried out by business actors with the GCPL Law in implementing a bundling system that forces consumers to buy products in packages. This emphasizes empowering weak consumers in the face of adverse conditions. Often the product sales strategies found can benefit consumers in shopping, thus making this research different from previous studies. The results showed that according to the GCPL, business actors should not force consumers to buy products with a bundling system, because it can reduce consumer comfort when shopping. In implementing the bundling system, it is natural to pay attention to the GCPL so as not to cause harm to consumers. Consumers also have the right to security, honest information about product conditions, and the right to choose goods according to the exchange rate stated in the GCPL Law. Conclusion, consumer protection can be carried out through LPKSM supervision seen from the obedience of business actors as prevention. Legal efforts that can be taken by consumers include peaceful settlement, BPSK, or court through a tort lawsuit.